Learning to philosophize - "Emmet, E.R." ("Middlesex,Eng.", 1984)
'Sure in the independence, confident of the future of Britain, the Daily Express is rooted in the hearts of the people. It is Britain's greatest newspaper.' Daily Express 31 December 1960 Discuss the possible criteria for this claim. With this kind of homely exercise the reader of this entertaining Pelican is encouraged to practise the strokes of philosophy$1! = (BThe author initiates the beginner into the world of ideas and words with an examination of the use of language, and in subsequent chapters deals with the handling of concepts, considers the fundamental step of asking the right question, and examines the nature of value judgements. It is only in the last two chapters that the reader is very gently led up to the brink of more difficult problems in the discussions of Appearance and Reality and of Free Will and Determinism. In short, [this book] with its lively selection of quotations from very varied sources, provides a 'think-it-yourself handbook' for the application of logic and philosophy in daily life.s
Keywords: "Learning, Psychology"